The Political Economy of Compensatory Redistribution: Unemployment, Inequality and Policy Choice - Jonas Pontusson; David Weisstanner (Luxembourg Income Study (LIS), 2016)
This paper explores common trends in inequality and redistribution across OECD countries from the late 1980s to 2013. Low-end inequality rises during economic downturns while rising top-end inequality is associated with economic growth. Most countries retreated from redistribution from the mid-1990s until the onset of the Great Recession and compensatory redistribution in response to rising unemployment was weaker in 2008-13 than in the first half of the 1990s. As unemployment and poverty risk have become increasingly become concentrated among workers with low education, middle-income opinion has become more permissive of cuts in unemployment insurance generosity and income assistance to the poor. At constant generosity, the expansion of more precarious forms of employment reduces compensatory redistribution during downturns because temporary employees do not have the same access to unemployment benefits as permanent employees.
Keywords: 330; comparative political economy; income inequality; redistribution; unemployment; poverty risk